Cultivation of Arthrospira (Spirulina) platensis using low cost medium supplemented with Lac wastewater - Pamon Pumas (2018)
© 2016, Chiang Mai University. All rights reserved. Arthrospira or Spirulina is a well-known food supplement; however, the cost of the culture medium is pricey. Thus, the aim of this paper is to cultivate Arthrospira (Spirulina) platensis using a low cost medium (CMU02) supplement with lac wastewater. Four samples of lac wastewater from different lac production processes were supplemented to the CMU02 medium. The growth, biomass production, protein and pigment contents, as well as the production cost of each treatment were evaluated. It was found that the primary positive effect of the lac wastewater after water treatment was the increased biomass concentration that was recorded as high as 0.624 g.L-1 with a protein content of 59.11 g.100 g dry weight-1. Carotenoid and phycocyanin contents of 0.17 mg.g dry weight-1 and 71.30 mg.g dry weight-1, respectively, were also achieved. Lac wastewater could reduce the estimated cultivation cost by as much as 4.43 fold when compared with the Zarrouk medium. These findings indicate that lac wastewater can be used as a cost-saving supplement in large-scale cultivation systems.